Evaluation of the behavior of climatic elements in the Mantaro Valley from 2000 to 2020, Department of Junín - Sandoval Apolinario, Fiorella Melissa (2024)
In recent years, climate change has doubled its impact worldwide due to different anthropogenic activities, altering the climatic variability of atmospheric elements and meteorological phenomena that play a relevant role in establishing life on the planet. Thus, the behaviour of climatic elements was evaluated and analysed between the period 2000-2020 in the provinces of Chupaca, Huancayo and Concepción del Valle del Mantaro, by means of the synoptic climatology method using MATLAB software to process hydrometeorological data (TX, TI, RR and RH) provided by SENAMHI. The behaviour of these variables resulted in an increase from -0.5°C to 6°C of TI, TX increased the value of the year 2000-2020 with a +6°C and the amplitude of the values of the distribution of the whisker box, regarding RR from the year 2011-2020 the value of 500 mm decreased to 200 mm in the station "F" while the value of RH decreased and was maintained in the station "C, B, A" because there was no significant increase in temperature to heat the air. Thus, the analysed data evidences and reinforces the variation of the climate system in the values of TX, TI, RR and RH.